KONSEP NILAI KENYAMANAN RUANG DARI SUDUT PANDANG ANAK-ANAK DI KECAMATAN KOTABUMI - Nisfi Eka Sulistiorini; Lutfi Setianingrum (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2021)
Comfort guarantees are often seen as a problem for users of public open spaces, especially children. Convenience is an indicator of the level of habitability of a public space. Along with the development of the city, the value of comfort is something that allegedly shows the character of the city. The character of the city is an assessment of what is felt by users (children) who carry out activities in space. Therefore, more attention is needed to the design factors that children need to support their activities. For this reason, an in-depth study of the concept of space comfort values ​​is needed from the point of view of children in Kotabumi District. The methodology in this study uses qualitative inductive analysis with a naturalistic approach. From the analysis, it can be seen that the value of space comfort that is formed from the point of view of children is formed from: 1) Values ​​instilled by parents; 2) Activities carried out by children; and 3) Child social interactions. The concept of the value of space comfort gives birth to criteria for a comfortable space for children. The criteria are among others: 1) Space that has a location not far from the child's residence; 2) Spaces that have ample space and cool conditions so that children can freely do activities, such as playing and learning; 3) Space that can accommodate for each age group of children; 4) Space that can be enjoyed by children without being charged (free); and 5) Spaces consisting of various kinds of games according to the child's age group. Based on this, it is expected that there will be an effort to consider the government in the process of optimizing Taman Sahabat as a public open space for children by considering the criteria of comfortable space according to children in Kotabumi District.